Peningkatan Budaya Literasi Melalui Program Pojok Edukasi pada SD Negeri 34 Sungai Kakap - Patrisius Piki; Dezky Surya Anugrah; Steven Ludoviko Andro Batuahgagas; Susianto Susianto; Samuel Melanus (Pusat Riset dan Inovasi Nasional, 2025)
Reading interest among the Indonesian population remains considerably low. According to data from UNESCO, only around 0.001 percent of Indonesians demonstrate a high level of reading interest, equivalent to just 1 in 1,000 people. Another study, “World’s Most Literate Nations” by Central Connecticut State University, also indicates Indonesia’s low literacy ranking—60th out of 61 countries. This situation is further exacerbated by the 2022 PISA assessment results, which place Indonesia at 71st out of 81 participating countries in reading proficiency. One contributing factor to the weak literacy rate is the automatic grade promotion policy implemented during the COVID-19 pandemic, which allowed students to advance to the next grade level without mastering basic reading skills. This issue was observed at SD Negeri 34 Sungai Kakap, West Kalimantan, where several students from grades 1 to 5 were still unable to read properly. In response to this condition, a reading corner program was designed as an initiative to foster a reading culture by providing students with easy access to books before, during, and after class. The program is expected to improve both reading interest and reading skills among children in the area.